Variation in Community-Level Trophic Niches of Soil Microarthropods With Conversion of Tropical Rainforest Into Plantation Systems as Indicated by Stable Isotopes (15N, 13C) - Krause, Alena; Sandmann, Dorothee; Potapov, Anton; Ermilov, Sergey; Widyastuti, Rahayu; Haneda, Noor Farikhah; Scheu, Stefan; Maraun, Mark (Frontiers in Ecology and Evolution, 2021)
Land-use change is threatening biodiversity worldwide and is predicted to increase in the next decades, especially in tropical regions. Most studies focused on the response of single or few species to land-use change, only few investigated the response of entire communities. In particular the response of belowground communities to changes in land use received little attention. Oribatid mites (Oribatida, Acari) are among the most abundant soil animals, involved in decomposition processes and nutrient cycling. Oribatid mite species span a wide range of trophic niches and are known to sensitively respond to changes in land use. Here, we investigated shifts in the community-level trophic niche of oribatid mites with the conversion of rainforest into rubber and oil palm plantations. Due to a wider range of resources in more natural ecosystems, we expected the community-level trophic niche to shrink with conversion of rainforest into plantations. As the conversion of rainforest into plantations is associated with reduced availability of litter resources, we expected the average trophic level (indicated by the 15N/14N ratio) to be higher and basal resources (indicated by the 13C/12C ratio) to shift towards living plant material in rubber and oil palm plantations. Our analysis showed that community-level trophic niches in rainforest and rubber agroforest (“jungle rubber”) were separated from that in monoculture plantation systems, indicating a trophic niche shift with land-use intensification. As hypothesized, oribatid mites shifted their diet towards predation and/or scavenging and towards the plant-based energy channel with transformation of rainforest into plantations. Exceptionally low minimum 13C/12C ratios in rubber plantations suggest that certain oribatid mite species in this land-use system use resources not available in the other studied ecosystems. We detected high isotopic uniqueness in oil palm plantations suggesting a low trophic redundancy and thus high vulnerability of trophic functioning in this system in comparison to rainforest. Overall, the results suggest that the conversion of rainforest into plantations is associated with pronounced shifts in community-level trophic niches of mesofauna detritivores with potential major consequences for the functioning of the decomposer system.